The Influence of Brand Image and Ethnic Identity on Decision to Study at Politeknik Unggul LP3M - Ratih Amelia (Journal of Business Integration Competitive, 2024)
This study aims to analyze the influence of brand image and ethnic identity on the decision to study at Politeknik Unggul LP3M. Prospective students form a perception of brand image based on the reputation and image of higher education institutions, and their awareness of their ethnic group influences their preferences and decisions when choosing an educational institution. This study employs a quantitative approach, utilizing a survey method that involves 200 respondents, specifically prospective students who are considering Politeknik Unggul LP3M as their educational choice. We collected data using a questionnaire, measured using a Likert scale, and analyzed the results using multiple linear regression. The results of the study show that brand image and ethnic identity have a significant influence on the decisiThe study demonstrates that brand image dominates the decision-making process, with ethnic identity following closely behind. decision, followed by ethnic identity. The management of Politeknik Unggul LP3M expects these findings to provide insight into formulating more effective marketing strategies by considering the factors that influence prospective students' decisions